2010
DOI: 10.1186/1471-2458-10-20
|View full text |Cite|
|
Sign up to set email alerts
|

Adverse childhood experiences are associated with the risk of lung cancer: a prospective cohort study

Abstract: BackgroundStrong relationships between exposure to childhood traumatic stressors and smoking behaviours inspire the question whether these adverse childhood experiences (ACEs) are associated with an increased risk of lung cancer during adulthood.MethodsBaseline survey data on health behaviours, health status and exposure to adverse childhood experiences (ACEs) were collected from 17,337 adults during 1995-1997. ACEs included abuse (emotional, physical, sexual), witnessing domestic violence, parental separation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
226
4
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 326 publications
(240 citation statements)
references
References 39 publications
7
226
4
3
Order By: Relevance
“…By using PCA, we were able to use the data to derive three components of ACEs. Brown et al (2010) found a positive association between ACEs and risk of lung cancer, which coincides with the findings in the current study. However, the current study considered prevalence of all cancers overall, in childhood and adulthood, in a cross-sectional study with a population-based sample while Brown et al (2010) looked at incident lung cancer using a prospective study design [15].…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…By using PCA, we were able to use the data to derive three components of ACEs. Brown et al (2010) found a positive association between ACEs and risk of lung cancer, which coincides with the findings in the current study. However, the current study considered prevalence of all cancers overall, in childhood and adulthood, in a cross-sectional study with a population-based sample while Brown et al (2010) looked at incident lung cancer using a prospective study design [15].…”
Section: Discussionsupporting
confidence: 93%
“…However, the increase in the risk of lung cancer could only be partially explained by the relationship between ACEs and smoking. Therefore, this finding suggests that the association between ACEs and cancer may be attributable to other mechanisms in which stressors and trauma during childhood negatively affect health [15]. In a prospective study, adverse events occurring between ages six and eight, and cumulative adversity from birth to age eight were found to be associated with inflammation at age ten [23].…”
Section: Introductionmentioning
confidence: 89%
See 3 more Smart Citations